Pengembangan Sistem Penyusunan Naskah Soal Pilihan Ganda Secara Acak Berbasis Web (Studi Kasus: Kelompok Jabatan Fungsional Dosen Rekayasa Perangkat Lunak Program Studi Teknik Informatika Fakultas Ilmu Komputer Universitas Brawijaya) - Umi Hanik Pratiwi; Tri Astoto Kurniawan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Learning evaluation using multiple choice question paper is widely used because it is more effective at measuring learning outcomes and can cover more subjects. In 2017, there was a research to build multiple choice exam question bank management system at Faculty of Computer Science Brawijaya University. This research helps to reduce the possibility of similar question being proposed by different lecturers. However the research was not able to generate multiple choice question paper. The Course Lecturer Coordinator must select the questions one by one at question bank to generate a question paper. The question paper made by Course Lecturer Coordinator must meet the learning outcomes that have been set at the beginning of semester. Therefore, the question paper must have topics and question difficulty level which corresponds to the learning outcomes. This made it difficult to generate question paper. A web-based randomized multiple choice question paper generation system was developed to resolve this problem. The system development was done with waterfall software development model using object-oriented approach. This system had been tested using unit, integration, and validation testing. White-box testing was used in unit and integration testing, while black-box testing was used in validation testing. All of the tests performed to the system shows valid results.